Peran Hukum Islam Terhadap Hukum Positif di Indonesia - Fadhil Citra Darmakusuma; Muhammad Afrizal Habibie; Muhammad Zidan Ramadhan; Nauval Athalah Ramadani; Raja Huwaidi Kamil; Baidhowi (CV. ITTC INDONESIA, 2025)
This study examines the role of Islamic law in the formation and development of positive law in Indonesia, which historically, philosophically, and constitutionally holds a crucial position within the national legal system. As an integral part of Indonesian society, Islamic law has contributed to various aspects of regulation, particularly in the areas of family law, Islamic economics, and Islamic philanthropy. Through an analysis of regulations such as the Marriage Law, the Zakat Law, the Waqf Law, and the Islamic Banking Law, this study demonstrates that sharia principles such as justice, welfare, and legal certainty are relevant to the objectives of national law, which is based on Pancasila and the 1945 Constitution. However, harmonization between Islamic law and positive law still faces challenges, including legal pluralism, differences in interpretation, and institutional limitations. Based on this discussion, this study recommends strengthening sharia-based legislation, increasing the capacity of Islamic legal institutions, legal literacy, and contextual ijtihad to ensure that Islamic law plays a growing role in the development of a just, modern, and Indonesian-characterized national law.